Numerical Insights into Wide-Angle, Phase-Controlled Optical Absorption in a Single-Layer Vanadium Dioxide Structure - Abida Parveen; Ahsan Irshad; Deepika Tyagi; Mehboob Alam; Shakeel Ahmed; Keyu Tao; Zhengbiao Ouyang (Crystals)
Vanadium dioxide (VO2) is a well-known phase-change material that exhibits a thermally driven insulator-to-metal transition (IMT) near 68 °C, leading to significant changes in its electrical and optical properties. This transition is governed by structural modifications in the VO2 crystal lattice, enabling dynamic control over absorption, reflection, and transmission. Despite its promising tunability, VO2-based optical absorbers face challenges such as a narrow IMT temperature window, intrinsic optical losses, and fabrication complexities associated with multilayer designs. In this work, we propose and numerically investigate a single-layer VO2-based optical absorber for the visible spectrum using full-wave electromagnetic simulations. The proposed absorber achieves nearly 95% absorption at 25 °C (insulating phase), which drops below 5% at 80 °C (metallic phase), demonstrating exceptional optical tunability. This behavior is attributed to VO2’s high refractive index in the insulating state, which enhances resonant light trapping. Unlike conventional multilayer absorbers, our single-layer VO2 design eliminates structural complexity, simplifying fabrication and reducing material costs. These findings highlight the potential of VO2-based crystalline materials for tunable and energy-efficient optical absorption, making them suitable for adaptive optics, smart windows, and optical switching applications. The numerical results presented in this study contribute to the ongoing development of crystal-based phase-transition materials for next-generation reconfigurable photonic and optoelectronic devices.